Pollution, sources, and ecological-health risks of polycyclic aromatic hydrocarbons in coastal waters along coastline of China. Issue 4 (20th April 2020) - Lu, Jian; Zhang, Cui; Wu, Jun; Lin, Yichen; Zhang, Yuxuan; Yu, Xiaobin; Zhang, Zhenhua
Abstract: This study investigated the distribution, sources, and potential risks of polycyclic aromatic hydrocarbons (PAHs) in coastal waters along over 18, 000 km of coastline in China. Concentrations of PAHs in coastal waters ranged from 141.99 to 717.72 ng/L. Approximately 84.38% of sampling sites were determined at moderate PAH pollution level. PAHs in coastal waters at most of sampling sites mainly originated from combustion based on characteristic ratios of PAHs. Ecological risks posed by PAHs in coastal waters were evaluated as high level at 59.38% of sampling sites and moderate level at 40.63% of sampling sites although toxic equivalent quotients of PAHs only ranged from 2.86 to 126.52 ng/L benzo[a]pyrene that was not detected at all sampling sites. Maximal cancer risk/hazard quotient of total PAHs in coastal waters for adults and children reached 6.34 × 10 −4 /5.85 × 10 −2 and 2.25 × 10 −3 /7.72 × 10 −2, respectively. PAHs exerted high cancer risks for children at 31.25% of sampling sites. Health risks posed by PAHs in coastal waters of this study were higher than those of Japan, Belgium, Greece, Italy, Spain, USA, and Australia, but much lower than those of Singapore, Iran, Brazil, and Egypt. These findings indicate that PAH pollution has become a crucial stress affecting the sustainable development of coastal regions.